Multiculturalism in Pesantren: The Dialectic of Islamic Education between Tradition and Modernity - Mubarok, Husni (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines multiculturalism in pesantren by exploring the dialectical relationship between traditional Islamic education and modern educational demands. Employing a qualitative research approach with a case study design, data were collected through in-depth interviews, participant observation, and document analysis involving kyai, teachers, and santri from diverse cultural backgrounds. The findings reveal that pesantren function as multicultural educational spaces where diversity in ethnicity, language, and regional origin is integrated into daily religious and social practices. Multicultural values are cultivated through communal living, inclusive pedagogical strategies, and leadership grounded in Islamic ethics. Furthermore, strong leadership and institutional support play a crucial role in sustaining multicultural practices, while the negotiation between tradition and modernity enables pesantren to remain relevant without losing their religious identity. This study concludes that pesantren contribute significantly to the development of inclusive and moderate Islamic education by transforming cultural diversity into moral and social capital. The findings offer important insights for strengthening multicultural education within Islamic educational institutions in plural societies.